Passivated perovskite crystallization and stability in organic–inorganic halide solar cells by doping a donor polymer. Issue 6 (17th January 2017) - Zhang, Cong-Cong; Li, Meng; Wang, Zhao-Kui; Jiang, Yu-Rong; Liu, Hai-Rui; Yang, Ying-Guo; Gao, Xing-Yu; Ma, Heng
Abstract : Photovoltaic performance of planar perovskite solar cells has been improved by mixing CH3 NH3 PbI x Cl3− x and a donor polymer [ N -9′′-hepta-decanyl-2, 7-carbazole- alt -5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiaz-ole)]. Abstract : Photovoltaic performance of planar perovskite hybrid solar cells (pero-HSCs) has been improved by mixing CH3 NH3 PbI x Cl3− x and an electron donor polymer [ N -9′′-hepta-decanyl-2, 7-carbazole- alt -5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiaz-ole)] (PCDTBT). PCDTBT contains lone pairs of electrons due to the presence of S and N atoms, which could passivate the trap states of the perovskite layer and thus reduce the number of film defects. A Stonehenge-like structure could be formed by the interaction of CH3 NH3 PbI x Cl3− x and PCDTBT, developing more ordered orientation crystallization and a high quality film morphology. The doped solar cells are characterized by their excellent photovoltaic properties and enhanced stability. When the doping concentration is 0.3 mg mL −1, the fabricated solar cell device exhibits an outstanding power conversion efficiency (PCE) of 15.76%, which represents a significant improvement with respect to the magnitude of 16% obtained for the reference device.